FESTIVAL LIMA GUNUNG DI MAGELANG - Joko Aswoyo (Institut Seni Indonesia Surakarta, 2013)
This article aims to describe the social and cultural event called Festival Lima Gunung(FLG). This festival is an art performance that is held by and for the agricultural communitieswho live on the slopes of the mountains Merapi, Merbabu, Andong, Sumbing, and Menoreh.The performance is inspired by art forms that are used for ritual purposes in the villages on thesefive mountains. The festival is managed independently without any support from elsewhere.Observation, direct involvement, and interviews were used to gather data related to this festival.The results showed that this event has a significant and varied influence on the development ofthe arts among the agricultural communities on these five mountains.